2017
DOI: 10.1371/journal.pone.0171394
|View full text |Cite
|
Sign up to set email alerts
|

Allergic rhinitis, atopic dermatitis, and asthma are associated with differences in school performance among Korean adolescents

Abstract: Several studies have reported negative relations between allergic diseases and school performance but have not simultaneously considered various allergic diseases, including allergic rhinitis, asthma, and atopic dermatitis, and only examined a limited number of participants. The present study investigated the associations of allergic rhinitis, asthma, and atopic dermatitis with school performance in a large, representative Korean adolescent population. A total of 299,695 7th through 12th grade students partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 36 publications
4
18
0
7
Order By: Relevance
“…The results for asthma support a 2005 review investigating asthma in children and academic performance concluding that any association was weak or nonexistent, as well as the null findings of two subsequent studies: a Swedish study on adolescents, and a US study on children aged 8‐17 . However, two more recent studies have found an association between ever, school age and diagnosed asthma with worse academic performance. The larger of these studies by Kim et al included 299 695 children from years 7‐12, and although this is the largest study in this field to date, the limitation of this study was that the participants were voluntary and self‐reported on both exposures and academic performance, hence increasing the risk for selection and measurement bias.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The results for asthma support a 2005 review investigating asthma in children and academic performance concluding that any association was weak or nonexistent, as well as the null findings of two subsequent studies: a Swedish study on adolescents, and a US study on children aged 8‐17 . However, two more recent studies have found an association between ever, school age and diagnosed asthma with worse academic performance. The larger of these studies by Kim et al included 299 695 children from years 7‐12, and although this is the largest study in this field to date, the limitation of this study was that the participants were voluntary and self‐reported on both exposures and academic performance, hence increasing the risk for selection and measurement bias.…”
Section: Discussionsupporting
confidence: 72%
“…Although asthma has been shown to be associated with increased absenteeism and in turn absenteeism has been shown to be associated with reduced academic performance, the direct association between asthma and academic performance is unclear. Several studies have found a negative association between asthma and academic performance, while others have found none . This could be because of the heterogeneity of asthma and that most cases are mild and controlled which may not influence learning and cognition, where as other phenotypes of asthma such as uncontrolled, severe or late onset asthma may have a more obvious impact on learning and performance .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Hirsh and Inzlicht (2010) showed that reduced error processing was related to worse academic performance. Given that dyspnea could potentially impair error processing, this might subsequently relate to reduced academic success, for example, in students with asthma who have been demonstrated to show impaired academic performance (Kim, Kim, Park, Kim, & Choi, 2017;Krenitsky-Korn, 2011;Moonie, Sterling, Figgs, & Castro, 2008). In view of these potential negative consequences that reduced error processing caused by dyspnea could have, we aimed at testing the effect of dyspnea on error processing.…”
mentioning
confidence: 99%
“…A recent study found that children who do not use mouth breathing exhibit better reading comprehension, arithmetic skills, and working memory function when compared with children who use mouth breathing (Kuroishi et al, 2015). Moreover, adenoidal hypertrophy and allergic rhinitis were found to lead to poor academic ability (Fensterseifer, Carpes, Weckx, & Martha, 2013;Walker et al, 2007) and high stress levels (Kim, Kim, Park, Kim, & Choi, 2017) during adolescence. Furthermore, a previous study showed that stress induces hippocampal atrophy and memory loss (Sapolsky, 2000).…”
mentioning
confidence: 99%